Provenance dan Implikasi Tektonik Batupasir Formasi Sawahtambang, Kabupaten Sijunjung, Sumatra Barat - Helen Dwi Putri; Budhi Setiawan; Yogie Zulkurnia Rochmana (Universitas Halu Oleo, 2024)
The Sawahtambang Formation in Sijunjung Regency, West Sumatra, is primarily composed of thick sandstones, which are of significant interest due to their potential as oil and gas reservoirs. However, the mineralogical and petrographic characteristics, as well as the depositional and tectonic origins of these sandstones, remain poorly understood, particularly in relation to the tectonic processes that influenced their formation. This knowledge gap poses challenges for accurate geological interpretation and resource assessment. The objective of this study is to investigate the mineral composition, petrographic properties, and provenance of the sandstones from the Sawahtambang Formation. The methodology employed includes petrographic analysis and provenance studies. The results of the provenance analysis indicate that the sandstones are derived from a Recycled Orogen source, suggesting that they were primarily formed in collision or subduction zones. This tectonic setting is characterized by a low feldspar and volcanic lithic content and a higher quartz content. The findings of this study contribute to a more comprehensive understanding of the geological information and origin of the Sawahtambang Formation sandstones in West Sumatra